Risk Factors for Adverse Birth Outcomes in the PROMISE 1077BF/1077FF Trial. (15th August 2019) - Sebikari, Dorothy; Farhad, Mona; Fenton, Terry; Owor, Maxensia; Stringer, Jeffrey S. A.; Qin, Min; Chakhtoura, Nahida; Chi, Benjamin H.; Saidi, Friday; Nevrekar, Neetal; Violari, Avy; Chipato, Tsungai; et al.
Abstract : Background: In the multicountry PROMISE 1077BF/1077FF trial, the risk of low birth weight (LBW; <2500 g) and preterm delivery (PTD; <37 weeks) was significantly higher among women initiating a protease inhibitor–based antiretroviral treatment (ART) regimen than those receiving ZDV alone. Among those assigned to a protease inhibitor regimen, tenofovir/emtricitabine was associated with the more severe outcomes of very LBW (<1500 g) and very PTD (<34 weeks) compared with zidovudine/lamivudine. Methods: We used multivariate logistic regression to further explore these treatment findings, taking into account demographic baseline clinical and postentry obstetrical factors. We evaluated individual adverse outcomes and composites that included stillbirth and early loss/spontaneous abortion. Results: Among 3333 women delivering at least 1 live infant, median maternal age at enrollment was 26 years; 661 (20%) were primiparous, and 110 (3.3%) reported at least 1 previous PTD. Seventeen percent of newborns were LBW, 1% were very LBW, 17% had PTD, and 3% had very PTD. Treatment allocation remained strongly associated with multiple adverse outcomes after controlling for other risk factors with both ART regimens exhibiting increased risk relative to ZDV alone. Other risk factors remaining significant in at least one of the multivariate models included the following: country, gestational age at entry, maternal age, maternal body mass index, previous PTD, history of alcohol use, baseline HIV viral titer, multiple gestation, and several obstetric risk factors. Conclusions: ART effects on adverse pregnancy outcomes reported in the randomized PROMISE trial remained strongly significant even after controlling for demographic, baseline clinical, and obstetrical risk factors, which were also associated with these outcomes. Abstract : Supplemental Digital Content is Available in the Text.